Assessment of Environmental and Economic Effects of Environmental Investment as a Decisions Problem - Myšková Renáta; Obršálová Ilona; Čenčík Petr; Šatera Karel (WSEAS Press, 2013)
This paper discusses the decision-making on environmental investments. The chosen case study is the waste water treatment plant with a focus on the reed bed sewage plant as a natural cleaning process. There are described different types of sewage treatment plants which can be included in the so called small sewage treatment plants category. Special attention is devoted to valuation of the reed bed sewage treatment plant (further RBSTP) and their environmental effects with regard to the concept of LCA. Features and functions of different sewage treatments are analysed and advantages and disadvantages of the RBSTP and their utilisation opportunities are discussed. Concepts of multicriteria decision methods are compared to the traditional methods of the economic efficiency evaluation.
Posuzování environmentálních a ekonomických dopadů investic do životního prostředí jako rozhodovací problém
Keywords: conventional and reed bed sewage treatment plants; efficiency; environmental and economic effects; environmental investment; Life Cycle Assessment; multi-criteria decision making; konvenční a kořenové čistírny odpadních vod; účinnost; environmentální a ekonomické dopady; investice do životního prostředí; Life Cycle Assessment; vícekriteriální rozhodování